Periodontal status in infertile women attending in vitro fertilization clinics - Godavarthi Lalasa; K Raja V Murthy; Sandhya Pavankumar; Gottimukkala Atchyuta Rama Raju (Wolters Kluwer Medknow Publications, 2014)
Background and Aim: Throughout a woman's life, hormonal influences affect therapeutic decision making in periodontics. A woman undergoing infertility treatment is given drugs to stimulate the ovaries, which lead to sustained higher levels of female sex hormones. The differing levels of these hormones, either in infertile women or in women undergoing therapy for infertility or in women who have conceived and delivered naturally could suggest a differing periodontal status amongst these three groups. Hence, this cross-sectional study was undertaken to assess and compare the periodontal status in the above three groups. Materials and Methods: 180 women including 60 women undergoing treatment for infertility (Group I), 60 women in whom infertility treatment had not yet been initiated (Group II) and 60 women who had conceived and delivered naturally (Group III-control group), of age range 25-35 years, were included. Clinical parameters including oral hygiene index simplified (OHI-S), gingival index, sulcus bleeding index (SBI) and clinical attachment loss (CAL) were assessed by a single examiner. Results: Despite similar OHI-S scores (P > 0.05) in all groups, women of Group I had significantly higher gingival inflammation and SBI (P < 0.05) as compared to women of Group II and Group III. Furthermore, the women in Group I and Group II had statistically higher CAL (P < 0.05) as compared with the control group. Conclusion: Within the limits of this study, it can be concluded that altered hormonal levels in infertile women undergoing assisted reproductive therapy and infertile women not undergoing this treatment can lead to increased attachment loss, suggesting that these women may require constant periodontal monitoring.